2006
DOI: 10.1007/s11325-006-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome is associated with metabolic syndrome rather than insulin resistance

Abstract: The aim of this study was to investigate cross-sectionally the prevalence and covariates of obstructive sleep apnea syndrome (OSAS) and its relationship to metabolic syndrome (MS), insulin resistance (IR), and coronary heart disease (CHD) in a population sample of 1,946 men and women representative of Turkish adults. OSAS was identified when habitual snoring and episodes of apnea were combined with another relevant symptom. MS was diagnosed based on modified criteria of the Adult Treatment Panel III and IR by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…20 On the other hand, rates if 3.5% and 6.1% were reported in France and Turkey, respectively. 1,12 Nevertheless, it should be noted that 90% of individuals with sleep apnea are undiagnosed. 21 The prevalence of habitual snoring was similar to findings from studies conducted in the USA (46%) and Malaysia (47.3%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 On the other hand, rates if 3.5% and 6.1% were reported in France and Turkey, respectively. 1,12 Nevertheless, it should be noted that 90% of individuals with sleep apnea are undiagnosed. 21 The prevalence of habitual snoring was similar to findings from studies conducted in the USA (46%) and Malaysia (47.3%).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] This has been confirmed in several studies. 1,8,[10][11][12][13]17 For example, obese individuals presented a risk of OSAS that was 10 times higher in the study by Salvador et al 27 There was also a strong relationship between these in the presence of confounding variables. On the basis of several studies, increased body weight can alter the normal upper airway mechanics during sleep through a variety of distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarises current definitions used in clinical studies on glucose metabolism and the MetS [48][49][50]. Table 2 summarises the available epidemiological studies on the association of SDB with IR and diabetes [16,[51][52][53][54][55][56][57][58][59][60][61][62]. In general population studies [25,63], snoring was shown to be a risk factor for the development of diabetes over 10 yrs independent of confounding factors.…”
Section: Physiological and Clinical Datamentioning
confidence: 99%
“…Snoring has been associated with higher risk of elevated glycosylated haemoglobin in premenopausal females, [4] and obstructive sleep apnoea (OSA) is linked to decreased insulin sensitivity [5]. Associations with the metabolic syndrome have been described [6,7], especially in females with severe OSA [7]. Despite the controversy in the development of new onset hypertension in patients with OSA in the Wisconsin Sleep Cohort Study [8] and the Sleep Heart Health Study [9], the association of OSA with hypertension was described in females [8,10,11].…”
mentioning
confidence: 99%